2016
DOI: 10.1038/nchem.2472
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of size-controlled liposomes on DNA nanotemplates

Abstract: Artificial lipid-bilayer membranes are valuable tools for the study of membrane structure and dynamics. For applications such as studying vesicular transport and drug delivery, there is a pressing need for artificial vesicles with controlled size. However, controlling vesicle size and shape with nanometer precision is challenging and approaches to achieve this can be heavily affected by lipid composition. Here we present a bio-inspired templating method to generate highly monodispersed sub-100nm unilamellar ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
252
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(253 citation statements)
references
References 48 publications
1
252
0
Order By: Relevance
“…These results clearly demonstrate that the DNA gel skeleton is a stabilizer of the artificial cells. Yang et al (39) reported DNA nanorings as templates to prepare nanometer-sized liposomes inside. Meanwhile, our DNA cytoskeleton mechanically supported the micrometer-sized liposomes from the inside.…”
Section: Resultsmentioning
confidence: 99%
“…These results clearly demonstrate that the DNA gel skeleton is a stabilizer of the artificial cells. Yang et al (39) reported DNA nanorings as templates to prepare nanometer-sized liposomes inside. Meanwhile, our DNA cytoskeleton mechanically supported the micrometer-sized liposomes from the inside.…”
Section: Resultsmentioning
confidence: 99%
“…15 DNA-assembled objects are of interest in the design and development of drug carriers, nanomachines, and other types of sophisticated nanomaterials. [16][17][18][19][20][21] The wide range of potential applications has led to considerable interest in the properties of oligonucleotides conjugated to polymers or lipophilic chains. [22][23][24][25][26][27][28][29][30] DNA conjugates often combine multiple self-assembly motifs enabling selective and orthogonal noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…If the Ac-SOD enzymosome could be prepared with circular micro-reservoirs, it could be markedly ample for expressing its action without disruption and also for a sustained release pattern of the enzyme. Similar modifications are done for peptides and polymers which makes an important drug targeting pathway [62]. Therefore the Acenzymosome could be a replaceable therapeutic agent for an intense effect in rheumatoid arthritis and longer flowing active particles for reperfusion pathologies.…”
Section: Acylated-sod Liposomesmentioning
confidence: 99%